On the financial sustainability of earnings-related pension schemes with "pay-as-you-go" financing and the role of government indexed bonds - Robalino Aguirre, David A., 1969- 1969- (Policy research working paper, 2006)
"In this paper the authors reconsider the idea of an earnings-related pension system with reserves invested in indexed government bonds as a mechanism to both ensure financial sustainability and improve security. They start by reviewing the characterization of the sustainable rate of return of an earnings-related pension system with pay-as-you-go financing. The authors show that current proxies for the sustainable rate, including the Swedish "gyroscope," are not stable and propose an alternative measure that depends on the growth of the buffer-stock and the pay-as-you-go asset. Using a simple one-sector macroeconomic model that embeds a notional account pension system they then show how GDP indexed government bonds, if combined with the right measure for the sustainable rate of return on contributions, could be used to generate a sustainable and secure earnings-related pension system, without becoming a fiscal burden. The proposal is particularly attractive for countries considering reforms to earnings-related systems that have accumulated a large implicit pension debt. In this case, the government bonds allow the financing of this debt in a transparent way. The proposed mechanism can also facilitate the transition to a fully-funded pension system when the government bonds are allowed to be traded. "--World Bank web site